2011
DOI: 10.1021/ja204817y
|View full text |Cite
|
Sign up to set email alerts
|

Contemporaneous Dual Catalysis: Chemoselective Cross-Coupling of Catalytic Vanadium–Allenoate and π-Allylpalladium Intermediates

Abstract: This paper presents a detailed investigation of a dual catalytic system that combines a vanadium-catalyzed Meyer-Schuster rearrangement and a palladium-catalyzed allylic alkylation. The implementation of this novel reaction relies on matching the formation rates of vanadium-allenoate and π-allylpalladium intermediates with their bimolecular coupling rate in order to minimize the undesired protonation or O-alkylation of the catalytically generated intermediates. Chemoselectivity in this dual catalytic process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…In 2011, however, Trost and Luan developed a unique synergistic approach to the synthesis of α-allyl-α,β-unsaturated ketones. 12 In previous studies, it was demonstrated that oxyvanadium catalysts 21 induces a 1,3-transposition of propargylic alcohols via nucleophilic vanadium-allenoate complex 22 (Eq 1). 13 The authors hypothesized that this catalytic nucleophile should also participate in a Tsuji-Trost allylation and couple with electrophilic π-allyl palladium complexes, forming α-allyl-α,β-unsaturated ketones.…”
Section: Carbonyl α-Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, however, Trost and Luan developed a unique synergistic approach to the synthesis of α-allyl-α,β-unsaturated ketones. 12 In previous studies, it was demonstrated that oxyvanadium catalysts 21 induces a 1,3-transposition of propargylic alcohols via nucleophilic vanadium-allenoate complex 22 (Eq 1). 13 The authors hypothesized that this catalytic nucleophile should also participate in a Tsuji-Trost allylation and couple with electrophilic π-allyl palladium complexes, forming α-allyl-α,β-unsaturated ketones.…”
Section: Carbonyl α-Functionalizationmentioning
confidence: 99%
“…Synergistic catalysis also has the potential to couple many types of irreversibly-formed, fleeting intermediates, as exemplified with Trost and Luan’s palladium-and vanadium-catalyzed synthesis of α-allylated-α,β-unsaturated ketones (Section 2.1, Scheme 8). 12 Both reactive intermediates are formed irreversibly, but still find each other and react to form the desired product before either engage in side reactions. As the concept of synergistic catalysis expands, the number of new and novel transformations this strategy provides will continue to grow.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“… 61 As they found that this aromatic activation was essential for the initial vanadium-catalysed rearrangement, later than year they expanded the scope to include aliphatic propargylic alcohols with an activating alkoxy group on the alkyne fragment. 62 …”
Section: Bimetallic Catalysis With Mononuclear Bond Breaking and Forminmentioning
confidence: 99%
“…Another example concerns the Pd-catalyzed Tsuji-Trost allylic substitutions and its combination with the V-catalyzed Meyer-Schuster rearrangement (Scheme 3) [21,22]. This coupling between propargylic alcohols and allylic carbonates promoted cooperatively by palladium and vanadium Fig.…”
Section: Pd-catalyzed Tsuji−trost Allylic Substitutionmentioning
confidence: 99%